A free surface flow solver based on an efficient improvement to a coupling method for interface computations. (15th October 2022) - Duy, Trong-Nguyen; Nguyen, Van-Tu; Phan, Thanh-Hoang; Kim, Dong-Hyun; Park, Warn-Gyu
Abstract: In this paper, a free surface flow solver based on an improved coupling method for practical, highly nonlinear, complex free-surface flows is presented. The coupling method which is based on taking the advantages of the continuity and boundedness properties of the conservative level-set (LS) function and the mass conservation property of the VOF approach is integrated into a Navier-Stokes solution to build a new free surface solver. The developed solver is then validated with several practical free surface flows of engineering applications. The test cases are selected so that the developed solver is challenged in simulations of flows with a large scale of density ratio, high-nonlinear, and complicated free surface in a wide range of engineering applications to explore its capability. The simulated flow fields are presented and compared with the available experimental data and of other numerical simulations. Good agreement is achieved implying the capability of the developed solver, and also exhibiting the ability to extend to other applications.